Les études stratégiques, défense d’une discipline - Fortmann, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
For some time now, within the sub-discipline of studies on security, a passionate debate has been opposing the supporters of research on peace and the theoreticians of strategic studies. This often emotional and controversial debate interferes considerably with the emergence of a truly scientific approach to the study of conflicts. It is from such an angle that this article reviews this dissension in strategic studies. It aims to assess and to criticize those arguments which dispute the legitimacy of the strategic approach in international relations. It is suggested that the factitious conflict between "pacifists" and "strategists" can and must be overcome in order for this sub-discipline to be recognised at truly university level.